Ice Shelf - Ocean Interaction in the Eastern Weddell Sea, Antarctica - Hattermann, Tore (Universitetet i Tromsø, 2012)
This thesis investigates the interaction of the Antarctic ice shelves along the coast of Dronning Maud Land with the ocean circulation in the Eastern Weddell Sea. A set of direct oceanic observations below the Fimbul Ice Shelf, which were acquired during three Antarctic field seasons in the austral summers 2009/10, 2010/11 and 2011/12, is a central element of the presented work. This new oceanographic dataset is complemented by a high-resolution state-of-the-art ice shelf - ocean circulation model. The results provide an estimate of the amount of basal melting at the Fimbul Ice Shelf, and revise the physical processes that determine the ocean heat fluxes over the East Antarctic continental slope. A major finding is that deep-ocean heat fluxes towards the ice are much more constrained than predicted by previous ocean models, causing substantially lower rates of basal melting than earlier suggested. The predicted basal melting is consistent with mass balance estimates from satellite data and implicates that the Fimbul Ice Shelf is currently not subject to rapid basal mass loss. Furthermore, the complex interplay of the processes within the coastal, frontal system, and their respective role in transporting heat for melting towards the ice is examined. The results emphasize the importance of oceanic eddies within the coastal circulation for controlling the inflow of Warm Deep Water into the ice shelf cavities. A realistic representation of the effect of the mesoscale eddy overturning is thus a crucial requirement in order to simulate basal melting along the Weddell Sea coast in the present and future climate. The results also imply that fresh, and solar-heated Antarctic Surface Water plays a central role for the ice shelf cavity exchange. Being produced by sea ice melting at the ocean surface, this water mass directly enters the cavity and increases the melting of shallow ice. Due to its buoyancy, the presence of Antarctic Surface Water also alters the coastal dynamics and regulates the inflow of warm water at depth, thus showing that a more detailed understanding of the role of this water mass for basal melting around Antarctica will need further attention. Finally, the results suggest a direct relationship between the simulated basal melting and only a few deterministic parameters of the coastal circulation, which is used to derive a simple parameterization of for basal melting at the Fimbul Ice Shelf.
Publication Title: Faculty of science and technology. Department of physics and technology Volume: Philosophiae Doctor Issue: DOKTOR-004 ISBN: 8282360783,9788282360784,8282360791,9788282360791
Keywords: Sørishavet; Weddellhavet; fysikk; fysisk oseanografi; isbrem; isshelf; klimaendringer

Two years of oceanic observations below the Fimbul Ice Shelf, Antarctica - Hattermann, Tore; Nøst, Ole Anders; Lilly, Jonathan M; Smedsrud, Lars H (Geophysical Research Letters, 2012)
The mechanisms by which heat is delivered to Antarctic ice shelves are a major source of uncertainty when assessing the response of the Antarctic ice sheet to climate change. Direct observations of the ice shelf-ocean interaction are extremely scarce and in many regions melt rates from ice shelf-ocean models are not constrained by measurements. Our two years of data (2010 and 2011) from three oceanic moorings below the Fimbul Ice Shelf in the Eastern Weddell Sea show cold cavity waters, with average temperatures of less than 0.1°C above the surface freezing point. This suggests low basal melt rates, consistent with remote sensing-based, steady-state mass balance estimates for this sector of the Antarctic coast. Oceanic heat for basal melting is found to be supplied by two sources of warm water entering below the ice: (i) eddy-like bursts of Modified Warm Deep Water that access the cavity at depth for eight months of the record; and (ii) fresh surface water that flushes parts of the ice base with temperatures above freezing during late summer and fall. This interplay of processes implies that basal melting at the Fimbul Ice Shelf cannot simply be parameterized by coastal deep ocean temperatures, but instead appears directly linked to both solar forcing at the surface as well as to the dynamics of the coastal current system.
Keywords: Sørishavet; Weddellhavet; fysisk oseanografi; innlandsis; isbrem; isshelf; klimaendringer; smelting

Hydrography and circulation below Fimbulisen Ice Shelf, East Antarctica, from 14 years of moored observations - Lauber, Julius; Hattermann, Tore; de Steur, Laura; Darelius, Elin; Fransson, Agneta (Ocean Sci., 2024)
Future mass loss from the East Antarctic Ice Sheet represents a major uncertainty in projections of future sea level rise. Recent studies have highlighted the potential vulnerability of the East Antarctic Ice Sheet to atmospheric and oceanic changes, but long-term observations inside the ice shelf cavities are rare. Here, we present new insights from observations from three oceanic moorings below Fimbulisen Ice Shelf from 2009 to 2023. We examine the characteristics of intrusions of modified Warm Deep Water (mWDW) across a sill connecting the cavity to the open ocean and investigate seasonal variability of the circulation and water masses inside the cavity using an optimum multiparameter analysis. In autumn, the water below the 345 m deep central part of the ice shelf is composed of up to 30 % solar-heated, buoyant Antarctic Surface Water (ASW), separating colder Ice Shelf Water from the ice base and affecting the cavity circulation on seasonal timescales. At depth, the occurrence of mWDW is associated with the advection of cyclonic eddies across the sill into the cavity. These eddies reach up to the ice base. The warm intrusions are observed most often from January to March and from September to November, and traces of mWDW-derived meltwater close to the ice base imply an overturning of these warm intrusions inside the cavity. We suggest that this timing is set by both the offshore thermocline depth and the interactions of the Antarctic Slope Current with the ice shelf topography over the continental slope. Our findings provide a better understanding of the interplay between shallow inflows of ASW contributions and deep inflows of mWDW for basal melting at Fimbulisen Ice Shelf, with implications for the potential vulnerability of the ice shelf to climate change.
Publisher: Copernicus Publications
Keywords: Dronning Maud Land; hydrografi; isshelf; klimaendringer; klimatologi; oseanografi

The Role of Tides in Ocean-Ice Shelf Interactions in the Southwestern Weddell Sea - Hausmann, Ute; Sallée, Jean-Baptiste; Jourdain, Nicolas; Mathiot, Pierre; Rousset, Clément; Madec, Gurvan; Deshayes, Julie; Hattermann, Tore (Journal of Geophysical Research: Oceans, 2020)
To investigate the role of tides in Weddell Sea ocean-ice shelf melt interactions, and resulting consequences for ocean properties and sea ice interactions, we develop a regional ocean-sea ice model configuration, with time-varying ocean boundary and atmospheric forcing, including the deep open ocean (at 2.5–4 km horizontal resolution), the southwestern continental shelf (≈2.5 km), and the adjacent cavities of eastern Weddell, Larsen, and Filchner-Ronne ice shelves (FRIS, 1.5–2.5 km). Simulated circulation, water mass, and ice shelf melt properties compare overall well with available open ocean and cavity observational knowledge. Tides are shown to enhance the kinetic energy of the time-varying flow in contact with the ice shelves, thereby increasing melt. This dynamically driven impact of tides on net melting is to almost 90% compensated by cooling through the meltwater that is produced but not quickly exported from regions of melting in the Weddell Sea cold-cavity regime. The resulting systematic tide-driven enhancement of both produced meltwater and its refreezing on ascending branches of, especially the FRIS, cavity circulation acts to increase net ice shelf melting (by 50% in respect to the state without tides, ≈50 Gt yr−1). In addition, tides also increase the melt-induced FRIS cavity circulation, and the meltwater export by the FRIS outflow. Simulations suggest attendant changes on the open-ocean southwestern continental shelf, characterized by overall freshening and small year-round sea ice thickening, as well as in the deep southwestern Weddell Sea in the form of a marked freshening of newly formed bottom waters.
Keywords: Sørishavet; Weddellhavet; brehylle; geofysikk; havis; isbrem; isshelf; klimaendringer; klimamodeller; klimatologi; oseanografi; sjøis; tidevann

Necessary Conditions for Warm Inflow Toward the Filchner Ice Shelf, Weddell Sea - Daae, Kjersti; Hattermann, Tore; Darelius, Elin Maria K; Mueller, Rachael D; Naughten, Kaitlin A; Timmermann, Ralph; Hellmer, Hartmut H (Geophysical Research Letters, 2020)
Understanding changes in Antarctic ice shelf basal melting is a major challenge for predicting future sea level. Currently, warm Circumpolar Deep Water surrounding Antarctica has limited access to the Weddell Sea continental shelf; consequently, melt rates at Filchner-Ronne Ice Shelf are low. However, large-scale model projections suggest that changes to the Antarctic Slope Front and the coastal circulation may enhance warm inflows within this century. We use a regional high-resolution ice shelf cavity and ocean circulation model to explore forcing changes that may trigger this regime shift. Our results suggest two necessary conditions for supporting a sustained warm inflow into the Filchner Ice Shelf cavity: (i) an extreme relaxation of the Antarctic Slope Front density gradient and (ii) substantial freshening of the dense shelf water. We also find that the on-shelf transport over the western Weddell Sea shelf is sensitive to the Filchner Trough overflow characteristics.
Keywords: Sørishavet; Weddellhavet; glasiologi; havnivåstigning; innlandsis; isbrem; isshelf; klimaendringer

Detailed Seismic Bathymetry Beneath Ekström Ice Shelf, Antarctica: Implications for Glacial History and Ice-Ocean Interaction - Smith, Emma C; Hattermann, Tore; Kuhn, Gerhard; Gaedicke, Christoph; Berger, Sophie; Drews, Reinhard; Ehlers, Todd A; Franke, Dieter; Gromig, Rapahel; Hofstede, Coen; Lambrecht, Astrid; Läufer, Andreas; et al. (Geophysical Research Letters, 2020)
The shape of ice shelf cavities are a major source of uncertainty in understanding ice-ocean interactions. This limits assessments of the response of the Antarctic ice sheets to climate change. Here we use vibroseis seismic reflection surveys to map the bathymetry beneath the Ekström Ice Shelf, Dronning Maud Land. The new bathymetry reveals an inland-sloping trough, reaching depths of 1,100 m below sea level, near the current grounding line, which we attribute to erosion by palaeo-ice streams. The trough does not cross-cut the outer parts of the continental shelf. Conductivity-temperature-depth profiles within the ice shelf cavity reveal the presence of cold water at shallower depths and tidal mixing at the ice shelf margins. It is unknown if warm water can access the trough. The new bathymetry is thought to be representative of many ice shelves in Dronning Maud Land, which together regulate the ice loss from a substantial area of East Antarctica.
Keywords: Dronning Maud Land; batymetri; brehylle; glasiologi; havnivåstigning; innlandsis; isbrem; issmelting; klimaendringer; kontinentalsokkel; seismologi

The Southern Ocean Freshwater Input from Antarctica (SOFIA) Initiative: scientific objectives and experimental design - Swart, Neil C.; Martin, Torge; Beadling, Rebecca; Chen, Jia-Jia; Danek, Christopher; England, Matthew H.; Farneti, Riccardo; Griffies, Stephen M.; Hattermann, Tore; Hauck, Judith; Haumann, F. Alexander; Jüling, André; et al. (Geoscientific Model Development, 2023)
As the climate warms, the grounded ice sheet and floating ice shelves surrounding Antarctica are melting and releasing additional freshwater into the Southern Ocean. Nonetheless, almost all existing coupled climate models have fixed ice sheets and lack the physics required to represent the dominant sources of Antarctic melt. These missing ice dynamics represent a key uncertainty that is typically unaccounted for in current global climate change projections. Previous modelling studies that have imposed additional Antarctic meltwater have demonstrated regional impacts on Southern Ocean stratification, circulation, and sea ice, as well as remote changes in atmospheric circulation, tropical precipitation, and global temperature. However, these previous studies have used widely varying rates of freshwater forcing, have been conducted using different climate models and configurations, and have reached differing conclusions on the magnitude of meltwater–climate feedbacks. The Southern Ocean Freshwater Input from Antarctica (SOFIA) initiative brings together a team of scientists to quantify the climate system response to Antarctic meltwater input along with key aspects of the uncertainty. In this paper, we summarize the state of knowledge on meltwater discharge from the Antarctic ice sheet and ice shelves to the Southern Ocean and explain the scientific objectives of our initiative. We propose a series of coupled and ocean–sea ice model experiments, including idealized meltwater experiments, historical experiments with observationally consistent meltwater input, and future scenarios driven by meltwater inputs derived from stand-alone ice sheet models. Through coordinating a multi-model ensemble of simulations using a common experimental design, open data archiving, and facilitating scientific collaboration, SOFIA aims to move the community toward better constraining our understanding of the climate system response to Antarctic melt.
Keywords: Sørishavet; geovitenskap; havnivåstigning; klimaendringer; klimamodeller; oseanografi

Reviews and syntheses: A framework to observe, understand and project ecosystem response to environmental change in the East Antarctic Southern Ocean - Gutt, Julian; Arndt, Stefanie; Barnes, David Keith Alan; Bornemann, Horst; Brey, Thomas; Eisen, Olaf; Flores, Hauke; Griffiths, Huw; Haas, Christian; Hain, Stefan; Hattermann, Tore; Held, Christoph; et al. (Biogeosciences (Online), 2022)
Systematic long-term studies on ecosystem dynamics are largely lacking from the East Antarctic Southern Ocean, although it is well recognized that they are indispensable to identify the ecological impacts and risks of environmental change. Here, we present a framework for establishing a long-term cross-disciplinary study on decadal timescales. We argue that the eastern Weddell Sea and the adjacent sea to the east, off Dronning Maud Land, is a particularly well suited area for such a study, since it is based on findings from previous expeditions to this region. Moreover, since climate and environmental change have so far been comparatively muted in this area, as in the eastern Antarctic in general, a systematic long-term study of its environmental and ecological state can provide a baseline of the current situation, which will be important for an assessment of future changes from their very onset, with consistent and comparable time series data underpinning and testing models and their projections. By establishing an Integrated East Antarctic Marine Research (IEAMaR) observatory, long-term changes in ocean dynamics, geochemistry, biodiversity, and ecosystem functions and services will be systematically explored and mapped through regular autonomous and ship-based synoptic surveys. An associated long-term ecological research (LTER) programme, including experimental and modelling work, will allow for studying climate-driven ecosystem changes and interactions with impacts arising from other anthropogenic activities. This integrative approach will provide a level of long-term data availability and ecosystem understanding that are imperative to determine, understand, and project the consequences of climate change and support a sound science-informed management of future conservation efforts in the Southern Ocean.
Publisher: Copernicus Publications
Keywords: Sørishavet; klimaendringer; miljøendringer; økosystemer

Future sea level change under CMIP5 and CMIP6 scenarios from the Greenland and Antarctic ice sheets - Payne, Antony J; Nowicki, Sophie; Abe-Ouchi, Ayako; Agosta, Cécile; Alexander, Patrick; Albrecht, Torsten; Asay-Davis, Xylar; Aschwanden, Andy; Barthel, Alice; Bracegirdle, Thomas J; Calov, Reinhard; Chambers, Christopher; et al. (Geophysical Research Letters, 2021)
Projections of the sea level contribution from the Greenland and Antarctic ice sheets rely on atmospheric and oceanic drivers obtained from climate models. The Earth System Models participating in the Coupled Model Intercomparison Project phase 6 (CMIP6) generally project greater future warming compared with the previous CMIP5 effort. Here we use four CMIP6 models and a selection of CMIP5 models to force multiple ice sheet models as part of the Ice Sheet Model Intercomparison Project for CMIP6 (ISMIP6). We find that the projected sea level contribution at 2100 from the ice sheet model ensemble under the CMIP6 scenarios falls within the CMIP5 range for the Antarctic ice sheet but is significantly increased for Greenland. Warmer atmosphere in CMIP6 models results in higher Greenland mass loss due to surface melt. For Antarctica, CMIP6 forcing is similar to CMIP5 and mass gain from increased snowfall counteracts increased loss due to ocean warming.
Keywords: Antarktis; glasiologi; havnivåstigning; innlandsis; klimaendringer; klimatologi; polarområdene; smelting

Projected land ice contributions to twenty-first-century sea level rise - Edwards, Tamsin L; Nowicki, Sophie; Marzeion, Ben; Hock, Regine; Goelzer, Heiko; Seroussi, Hélène; Jourdain, Nicolas C; Slater, Donald A; Turner, Fiona E; Smith, Christopher J; McKenna, Christine M; Simon, Erika; et al. (Nature, 2021)
The land ice contribution to global mean sea level rise has not yet been predicted using ice sheet and glacier models for the latest set of socio-economic scenarios, nor using coordinated exploration of uncertainties arising from the various computer models involved. Two recent international projects generated a large suite of projections using multiple models, but primarily used previous-generation scenarios and climate models, and could not fully explore known uncertainties. Here we estimate probability distributions for these projections under the new scenarios using statistical emulation of the ice sheet and glacier models. We find that limiting global warming to 1.5 degrees Celsius would halve the land ice contribution to twenty-first-century sea level rise, relative to current emissions pledges. The median decreases from 25 to 13 centimetres sea level equivalent (SLE) by 2100, with glaciers responsible for half the sea level contribution. The projected Antarctic contribution does not show a clear response to the emissions scenario, owing to uncertainties in the competing processes of increasing ice loss and snowfall accumulation in a warming climate. However, under risk-averse (pessimistic) assumptions, Antarctic ice loss could be five times higher, increasing the median land ice contribution to 42 centimetres SLE under current policies and pledges, with the 95th percentile projection exceeding half a metre even under 1.5 degrees Celsius warming. This would severely limit the possibility of mitigating future coastal flooding. Given this large range (between 13 centimetres SLE using the main projections under 1.5 degrees Celsius warming and 42 centimetres SLE using risk-averse projections under current pledges), adaptation planning for twenty-first-century sea level rise must account for a factor-of-three uncertainty in the land ice contribution until climate policies and the Antarctic response are further constrained.
Keywords: Antarktis; glasiologi; havnivåstigning; innlandsis; klimaendringer; klimatologi; polarområdene; smelting